DIGITAL SILENCE FOR YOUNG LEARNERS: INTEGRASI KECERDASAN BUATAN DALAM PEMBELAJARAN SILENT WAY UNTUK MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA SEKOLAH DASAR - Persada, Intan Dwi; Dewi Fitriani; Muhamad Furqon Al Hadiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Vocabulary mastery is a fundamental component of English language learning at the elementary school level. However, vocabulary instruction in schools remains largely teacher-centered, resulting in limited student engagement. The integration of the Silent Way method with Artificial Intelligence (AI) offers the potential to create a more autonomous, interactive, and context-rich learning experience. This study employed a quasi-experimental design with nonequivalent control groups. Students were divided into two groups: the experimental group, which received vocabulary instruction using an AI-assisted Digital Silent Way model, and the control group, which received conventional instruction. The vocabulary test instrument was developed based on established indicators, validated by experts, and tested for reliability prior to use. Data were collected through pre-tests and post-tests, and were analyzed using prerequisite statistical tests and mean difference tests to evaluate the effectiveness of the intervention. The findings indicate no significant difference between the groups at the outset. However, after the intervention, the experimental group demonstrated a marked improvement in vocabulary mastery compared to the control group. The most substantial gains were observed in the ability to use derived words accurately in context. These results suggest that the AI-assisted Digital Silent Way model effectively enhances students’ vocabulary acquisition and promotes active, self-directed learning. This study contributes to the development of innovative English language teaching strategies that align with technological advances and the learning needs of young learners. Keywords: Silent Way, Artificial Intelligence, Vocabulary Mastery